Framework Convention for the Protection of National Minorities of the Council of Europe - K. M. Fyodorov (Московский журнал международного права, 2007)
The article is devoted to the analysis of the Framework Convention for the Protection of National Minorities, which is the most comprehensive document of the Council of Europe in the field of protection of the national minorities’ rights. The Convention is considered to be the pioneering legally binding multilateral document aimed at the protection of national minorities as a whole, which specifically prescribes that this protection is part and parcel of the human rights protection. The Framework Convention is also very important for the elaboration of the acceptable definition of a “national minority” at the level of international law. It is noticed in the article that the text of the Framework Convention itself lacks the definition of a “national minority” and different approaches of the European countries’ representatives, who took part in the elaboration of the Framework Convention, towards formulating different definitions of a ‘national minority’ is analyzed.It is noticed in the article that the Convention contains mainly provisions of a programme character; therein goals and tasks that the parties undertake to fulfill are formulated. At the same time, it can be noticed that some provisions of the Framework Convention are capable of being applied directly. Some states have already confirmed their intention to abide by what can be called the programme of the direct application of the Framework Convention. The author concludes that, having affixed its signature to the international treaty, the state undertakes the obligation to act in accordance with the international standards.